2015
DOI: 10.1002/jcb.25276
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Bisphenol A Disrupts Mouse Fetal Liver Maturation in a Sex-Specific Manner

Abstract: Bisphenol A (BPA) is one of the most prevalent endocrine disrupting chemicals in the environment. Developmental exposure to BPA is known to be associated with liver dysfunction and diseases, such as hepatic steatosis, liver tumors, metabolic syndrome, and altered hepatic gene expression, and DNA methylation profiles. However, the effects of BPA on rodent liver development are unknown. The present study was undertaken to address this important question using the mouse as an experimental model. Pregnant mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…Several studies support that exposure to low-dose BPA leads to gender dimorphism and persistent disruption of maturation (Jasarevic et al, 2011;Beronius et al, 2013;DeBenedictis et al, 2016). In the present study, gestational and lactational exposure to low-dose BPA was found to induce persistent and more prominent changes in female offspring mice in terms of Th17 cell frequency, IL-17, IL-21, and RORγt mRNA expression.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies support that exposure to low-dose BPA leads to gender dimorphism and persistent disruption of maturation (Jasarevic et al, 2011;Beronius et al, 2013;DeBenedictis et al, 2016). In the present study, gestational and lactational exposure to low-dose BPA was found to induce persistent and more prominent changes in female offspring mice in terms of Th17 cell frequency, IL-17, IL-21, and RORγt mRNA expression.…”
Section: Discussionsupporting
confidence: 81%
“… , which is the master regulator in hepatocyte maturation ( Tan et al 2008 ), was down-regulated in the BPA50 male rat liver in the present study. A similar down-regulation of the transcription factor was reported to arise in mouse offspring after developmental BPA exposure; however, this occurred only in females ( DeBenedictis et al 2016 ). This reduction in , indicative of perturbations in hepatocyte development and a putative fetal origin for BPA-induced hepatic disorders, may not necessarily be sex-specific in general; instead, it may reflect a dose-dependent effect, a species-dependent effect, or both.…”
Section: Discussionsupporting
confidence: 68%
“…In a 2017 study, fetal livers were collected from the F1 generation (embryonic day E18.5) exposed to BPA in utero from E7.5 to E18.5, and gene expression of key hepatocyte maturation markers was assessed ( DeBenedictis, Guan & Yang, 2016 ). In particular, female mice changes were prominent and involved decreasing levels of mature hepatocyte markers, such as albumin and glycogen synthase (reduced 65% and 40%, respectively), decreased levels of C/EBP-alpha, the master transcription factor of hepatocyte maturation (reduced 50%), and increased levels of immature hepatocyte marker, α-fetoprotein (increased 43%).…”
Section: Survey Methodologymentioning
confidence: 99%